2015
DOI: 10.1016/j.bbr.2015.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine in the nucleus accumbens modulates the memory of social defeat in Syrian hamsters (Mesocricetus auratus)

Abstract: Conditioned defeat (CD) is a behavioral response that occurs in Syrian hamsters after they experience social defeat. Subsequently, defeated hamsters no longer produce territorial aggression but instead exhibit heightened levels of avoidance and submission, even when confronted with a smaller, non-aggressive intruder. Dopamine in the nucleus accumbens is hypothesized to act as a signal of salience for both rewarding and aversive stimuli to promote memory formation and appropriate behavioral responses to signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 67 publications
3
24
0
2
Order By: Relevance
“…In the social interaction test, one restrained animal briefly showed submissive behavior toward the intruder, and several restrained animals displayed aggressive behavior. These data are similar to agonistic behavior displayed by non-stressed hamsters in a resident-intruder paradigm, and indicate that acute restraint stress does not alter subsequent agonistic behavior [16, 19, 34, 37]. In the other behavioral tests, restrained animals tended to differ from non-restrained controls on some measures, but not always in a direction that would be considered anxiety-like.…”
Section: Resultssupporting
confidence: 67%
“…In the social interaction test, one restrained animal briefly showed submissive behavior toward the intruder, and several restrained animals displayed aggressive behavior. These data are similar to agonistic behavior displayed by non-stressed hamsters in a resident-intruder paradigm, and indicate that acute restraint stress does not alter subsequent agonistic behavior [16, 19, 34, 37]. In the other behavioral tests, restrained animals tended to differ from non-restrained controls on some measures, but not always in a direction that would be considered anxiety-like.…”
Section: Resultssupporting
confidence: 67%
“…Our customary defeat procedure uses a 15 min, inescapable defeat. This is a relatively mild social stressor, but it is sufficient to lead to robust and quantifiable behavioral changes observed during subsequent testing (Gray et al, 2015; Jasnow and Huhman, 2001; McCann and Huhman, 2012). In our original experiment, we did not observe a change in social avoidance in animals given VPA, but this could be due to a ceiling effect.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these findings strongly suggest that the effect of noradrenergic manipulations on aggression is mediated centrally, although more research is needed to determine where centrally the effects of social defeat on aggression are mediated. Previous research from our lab demonstrated that infusion of a GABA A receptor agonist (Luckett et al, 2012) or a dopamine receptor antagonist (Gray et al, 2015) into the nucleus accumbens before testing also restored aggression in previously defeated hamsters, so it is possible that the nucleus accumbens in a component of this circuit. Finally, we have demonstrated that the pharmacological inactivation of the lateral septum using muscimol also increases aggression in previously defeated hamsters, but it is important to note that this effect was limited to expression and not acquisition of CD and muscimol in the lateral septum increased aggression independent of whether the animals had been previously defeated or not (McDonald et al, 2012).…”
Section: Discussionmentioning
confidence: 99%